(untitled) (International Journal of Functional Research in Arts and Humanities (IJFRAH), 2025)
This study investigates the interplay between digital distrust and the adoption of electronic payment (e-payment) systems among rural adults in Cross River State, Nigeria, and its implications for fintech development. Utilizing a mixed-methods approach, data were collected from 200 rural adults through surveys and interviews to assess perceptions of trust, security, ease of use, and social influence on e-payment adoption. Findings reveal that high levels of digital distrust, driven by concerns over security (M = 3.8, SD = 0.9) and privacy (M = 3.6, SD = 1.0), significantly hinder e-payment adoption (β = -0.45, p < 0.01). Demographic analysis indicates that younger adults (18–30 years, 60%) and those with higher education (tertiary, 45%) exhibit greater trust in e-payments. Qualitative insights highlight cultural and infrastructural barriers, such as unreliable internet (80%) and limited digital literacy (65%). The study aligns with the Technology Acceptance Model, extending it to include trust as a critical factor in rural contexts. Recommendations include targeted digital literacy programs, enhanced cybersecurity measures, and community-based trust-building initiatives to foster e-payment adoption. These findings contribute to fintech development strategies by emphasizing the need to address distrust and infrastructure gaps to promote financial inclusion in rural Nigeria, supporting Sustainable Development Goals 8 and 10.